Answer:
x = 5
y = 3
Explanation:
Given:
Two equations are given.
![x + 2y = 11](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hryma5shd735xu36rx7eyqzosbid34km2g.png)
![x - 2y = -1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yyuj5itm8hk0wx8ebs0558dszdlmu0wu95.png)
We need to solve the system of equations.
Solution:
Rewrite the equation as:
----------(1)
----------(2)
First we solve the equation 1 for x.
----------(3)
plug in
in equation 2.
![11-2y-2y=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cqwqzgse9oom7hyrb921kcvt4u3idevw5u.png)
![11-4y=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ydsat9qyyvtlqjcr9d1w4b7wzgg8mzw4nj.png)
![4y=11+1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/llru0vwna8itzg1nuj11ky1n51m35tatt3.png)
![4y=12](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hhgsnim7wgz17piluqxdil84hedilrj825.png)
![y=(12)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jn8g1o5i56xbabw5g7n0u2lf5ppvpejg0x.png)
y = 3
Now, we substitute y = 3 in equation 3.
![x= 11-2(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iv38408qu89opdyvl2hruqz36lxsbsuqcn.png)
![x=11-6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hkb91ou26juiml0tshu7hatcngsa3pe6ey.png)
x = 5
Therefore, Value of x = 5 and y = 3.